2010
DOI: 10.1002/jhm.713
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations with healthcare‐associated complicated skin and skin structure infections: Impact of inappropriate empiric therapy on outcomes

Abstract: OBJECTIVE:Inappropriate empiric therapy worsens outcomes in certain healthcare-associated infections (HCAI). We studied the association of inappropriate empiric therapy with outcomes in patients with HCA complicated skin and skin structure infections (cSSSI). DESIGN:A single-center retrospective cohort study. PATIENTS: Hospitalized with a culture-positive cSSSI. MEASUREMENTS: We defined HCA-cSSSI as having !1 of these risk factors: (1) recent hospitalization, (2) recent antibiotics, (3) hemodialysis, (4) trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 17 publications
(24 reference statements)
1
40
0
1
Order By: Relevance
“…Available results are contradictory, possibly because of differences in study methods, definitions, and sample sizes. Zilberberg et al (28) reported that inappropriate therapy was independently associated with an excess hospital LOS (attributable LOS, 1.8 days; 95% CI, 1.4 to 2.3; P Ͻ 0.001), but not excess mortality, in 527 patients with health care-associated cSSTI. When patients were stratified by the presence of bacteremia, however, LOS differences were observed only in those with bacteremia.…”
Section: Discussionmentioning
confidence: 99%
“…Available results are contradictory, possibly because of differences in study methods, definitions, and sample sizes. Zilberberg et al (28) reported that inappropriate therapy was independently associated with an excess hospital LOS (attributable LOS, 1.8 days; 95% CI, 1.4 to 2.3; P Ͻ 0.001), but not excess mortality, in 527 patients with health care-associated cSSTI. When patients were stratified by the presence of bacteremia, however, LOS differences were observed only in those with bacteremia.…”
Section: Discussionmentioning
confidence: 99%
“…In the same data set analyzed in the current study, in a generalized linear model with the log-transformed LOS as the dependent variable, adjusting for multiple potential confounders, inappropriate empiric therapy conferred an attributable incremental increase in the hospital LOS of 1.8 days (95% CI 1.4-2.3) [6]. Together with the concerns about resistance pressures stemming from unnecessarily broad empiric coverage, the concern about the most efficient use of healthcare resources is a compelling impetus for developing risk stratification algorithms to use at the bedside, which can help clinicians develop appropriate coverage decisions that align with the goals of both best clinical care and antibiotic stewardship.…”
Section: Discussionmentioning
confidence: 88%
“…In the case of cSSSI, although inappropriate empiric therapy does not appear to elevate the risk of in-hospital death, it does alter hospital resource utilization [6]. In the same data set analyzed in the current study, in a generalized linear model with the log-transformed LOS as the dependent variable, adjusting for multiple potential confounders, inappropriate empiric therapy conferred an attributable incremental increase in the hospital LOS of 1.8 days (95% CI 1.4-2.3) [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations